Overcoming lignocellulose‐derived microbial inhibitors: advancing the Saccharomyces cerevisiae resistance toolbox. (25th August 2019) - Brandt, Bianca A.; Jansen, Trudy; Görgens, Johann F.; van Zyl, Willem H.
Abstract: Lignocellulose‐derived biofuels present an attractive carbon‐neutral alternative to fossil fuels amidst growing global energy and climate concerns. Bioethanol in particular, has been shown to be a viable additive to and / or replacement for petroleum in countries such as Brazil. The bioconversion of lignocellulose biomass to bioethanol is a developing technology with the yeast Saccharomyces cerevisiae playing a pivotal role in the fermentation‐based processes. This yeast however, is challenged to ferment under harsh conditions, specifically, during exposure to lignocellulose‐derived microbial inhibitors that are formed during pretreatment processes. This detrimentally affects biocatalyst performance, ultimately decreasing ethanol productivity and yield. To this end, S. cerevisiae strains are in development to increase the yeast microbial inhibitor resistance towards cost‐effective cellulosic bioethanol production. This review discusses the current status of inhibitor resistance in S. cerevisiae strains and perspectives on the future of multi‐tolerant phenotypes with a specific focus on existing and emerging strain development strategies designed to improve resistance phenotypes. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.